USING RANDOM TEXT STRATEGY IN IMPROVING READING COMPREHENSION ABILITY TO THE SECOND YEAR STUDENTS AT SMPN 1 PARIGI - Sri Nur Pajrianti; St. Asriati AM; Ilmiah (English Language Teaching Methodology, 2021)
Pre Experimental research with pre-test and post-test was used in the research. This study sample was class VII.B at SMPN 1 Parigi in academic year 2020/2021 which consist of 22 students. The research findings indicated that at SMPN 1 Parigi, random text strategy will enhance learner’s literal reading comprehension. It was proven by the mean score of pre-test was 46.36 and post-test was 77.77. The improvement of pre-test to be post-test was 67.75%. The result of improvement is also proved with t-test value. The researcher found that the value of t-test was 8.75 was greater that t-table 2.07. It was concluded that the use of the Random Text strategy at SMPN 1 Parigi was effective to improve the literal reading understanding of the students.